Production potential of congosignal grass (Brachiaria rosensis) in silvi-pastoral system in North East India - PANWAR, A S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during 2009–12 at ICAR Research Complex for NEH Region, Umiam, Meghalaya to study the performance of congosignal grass (Brachiaria rosensis L) under silvi-pastoral based agroforestry system in mid hill altitude of North East India. Congosignal grass was planted in open as well as intercrop with Simingtonia populanea and fertilized with 0, 30, 60 and 90 kg N/ha. The study showed that growth attributes and yield of congosignal was reduced under tee canopy, while crude protein content was 5.35 % higher under tree canopy. Dry fodder production was significantly higher in open (119.55 q/ha) than under tree canopy (87.46 q/ha). The content and uptake of NPK by congosignal grass were higher in open area, while organic carbon and residual NPK status improved under tree canopy. Application of nitrogen at increased level improved plant height, no. of tillers and leaf:stem ratio. The green and dry biomass yield was significantly higher with 60 kg N/ha. The content and uptake as well as residual NPK were significantly improved with 60 kg N/ha. The soil organic carbon improved under tree canopy than open. Higher gross and net return were recorded with application of 90 and 60 kg N/ha in open and tree canopy, respectively. The B:C ratio (3.08) was higher with 90 kg N/ha in open planting, while under tree canopy highest B:C ratio of 2.19 was recorded with 60 kg N/ha.